2016
DOI: 10.1016/j.jconrel.2016.03.036
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and pharmacodynamic study of a phospholipid-based phase separation gel for once a month administration of octreotide

Abstract: As a natural somatostatin analog, octreotide acetate (OCT) has been extensively used in cancer treatment and growth hormone related diseases. The clinical application of OCT, however, is greatly limited by its short half-life, rapid elimination and clearance in vivo. In the current study, a high content phospholipid-based phase separation gel platform (PPSG) was presented, which could be injected in the soluble state and underwent rapid phase-separation into a gel-like implant after a single subcutaneous injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 60 publications
(66 reference statements)
0
10
0
Order By: Relevance
“…11 The pharmacokinetics of octreotide have not been evaluated in horses, but the half-life of octreotide acetate solution was 12.6, 0.567, and 0.66 hour in rats, rabbits, and dogs, respectively, when administered via single subcutaneous injection at dosages of 20, 0.025, and 0.022 mg/kg, respectively. 12 Serum insulin concentrations decreased in response to subcutaneous injection of 50 lg SMS 201-995 (octreotide) in healthy human subjects, with subsequent increase in blood glucose concentrations. 13 Octreotide also lowered plasma glucagon concentrations and blunted the nocturnal rise in thyroid-stimulating hormone concentrations, but did not impact thyroid hormone or cortisol concentrations.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…11 The pharmacokinetics of octreotide have not been evaluated in horses, but the half-life of octreotide acetate solution was 12.6, 0.567, and 0.66 hour in rats, rabbits, and dogs, respectively, when administered via single subcutaneous injection at dosages of 20, 0.025, and 0.022 mg/kg, respectively. 12 Serum insulin concentrations decreased in response to subcutaneous injection of 50 lg SMS 201-995 (octreotide) in healthy human subjects, with subsequent increase in blood glucose concentrations. 13 Octreotide also lowered plasma glucagon concentrations and blunted the nocturnal rise in thyroid-stimulating hormone concentrations, but did not impact thyroid hormone or cortisol concentrations.…”
mentioning
confidence: 88%
“…The elimination half‐life of octreotide is approximately 1.5 hour after intravenous or subcutaneous administration in humans, and octreotide is 20 times more potent than SST when suppressing growth hormone secretion . The pharmacokinetics of octreotide have not been evaluated in horses, but the half‐life of octreotide acetate solution was 12.6, 0.567, and 0.66 hour in rats, rabbits, and dogs, respectively, when administered via single subcutaneous injection at dosages of 20, 0.025, and 0.022 mg/kg, respectively . Serum insulin concentrations decreased in response to subcutaneous injection of 50 μg SMS 201‐995 (octreotide) in healthy human subjects, with subsequent increase in blood glucose concentrations .…”
mentioning
confidence: 99%
“…In a previous study [26], OCT PPSG (C OCT = 5 mg/mL) and blank PPSG showed almost the same viscosity at the same temperature, and OCT PPSG transformed into a gel upon exposure to water. Both OCT (octapeptide, Mw = 1019.24) and TP5 (pentapeptide, Mw = 679.77) are low molecular weight peptides, and the drug concentrations in PPSG were relatively low (5 mg/mL).…”
Section: Resultsmentioning
confidence: 74%
“…In vitro release study An in vitro release study was conducted by dynamic dialysis in phosphate-buffered saline containing different concentrations of ethanol (0, 10, and 20%) [25,26]. Aliquots of 0.2 g of TP5-PPSG (TP5 concentration = 5.0 mg/mL) or 1.0 mL of TP5 (TP5 concentration = 1.0 mg/mL) solution were added to the dialysis bags (molecular weight cut-off = 8-14 kDa).…”
Section: Cells and Animalsmentioning
confidence: 99%
“…22 Compared with natural somatostatin, OCT shows more advantages, including longer half-life, more metabolic stability, and specificity. 23,24 Honokiol is an active compound isolated from traditional Chinese herb Magnolia officinalis. 25 It exhibits a variety of strong antitumor activities, including pro-apoptotic activity, anti-angiogenesis, anti-metastasis, and anti-proliferation in several types of tumors.…”
Section: Introductionmentioning
confidence: 99%